2006
DOI: 10.1088/0953-8984/18/34/002
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of the metal–oxygen bond in compositionally homogeneous, nanocrystalline zirconia–ceria solid solutions synthesized by a gel-combustion process

Abstract: Compositionally homogeneous ZrO2–CeO2 nanopowders have been characterized by Raman and extended x-ray absorption fine structure (EXAFS) spectroscopies. These techniques revealed a tetragonal-to-cubic phase transition as a function of CeO2 content, as observed in a previous synchrotron x-ray diffraction study. The tetragonal–cubic phase boundary was found to be at (85 ± 5) mol% CeO2. The EXAFS study demonstrated that this transition is related to a tetragonal-to-cubic symmetry change of the Zr–O first neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…6 displays this ratio, which exhibits a monotonous decrease with composition and became zero between 10 and 11 mol% Y 2 O 3 . This result indicates that the t /c transition in nanocrystalline ZrO 2 -Y 2 O 3 solid solutions occurs at (10.5 ± 0.5) mol% Y 2 O 3, in good agreement with the value independently determined by the above SXPD analysis following the intensity of the 1 1 2 Bragg peak and with the previous results reported by Yashima [22], a clearly linear behavior is observed over the whole composition range, thus confirming the compositionally homogeneous nature of the solid solutions prepared by the gel-combustion procedure [10][11][12][13][14][23][24][25][26][27][28][29]. The compositional homogeneity of materials synthesized by gel-combustion routes can be explained considering that the system remains homogeneous during the whole process and the final combustion step of the precursor gel proceeds very rapidly, thus preserving the compositional homogeneity in the as-reacted material.…”
Section: Raman Spectroscopysupporting
confidence: 90%
“…6 displays this ratio, which exhibits a monotonous decrease with composition and became zero between 10 and 11 mol% Y 2 O 3 . This result indicates that the t /c transition in nanocrystalline ZrO 2 -Y 2 O 3 solid solutions occurs at (10.5 ± 0.5) mol% Y 2 O 3, in good agreement with the value independently determined by the above SXPD analysis following the intensity of the 1 1 2 Bragg peak and with the previous results reported by Yashima [22], a clearly linear behavior is observed over the whole composition range, thus confirming the compositionally homogeneous nature of the solid solutions prepared by the gel-combustion procedure [10][11][12][13][14][23][24][25][26][27][28][29]. The compositional homogeneity of materials synthesized by gel-combustion routes can be explained considering that the system remains homogeneous during the whole process and the final combustion step of the precursor gel proceeds very rapidly, thus preserving the compositional homogeneity in the as-reacted material.…”
Section: Raman Spectroscopysupporting
confidence: 90%
“…Previous studies of the local atomic order of nanocrystalline ZrO 2 -CeO 2 solid solutions for samples with average crystallite sizes between 8 and 20 nm (Fá bregas et al, 2006) established a sevenfold coordination of Zr atoms over a wide range of compositions, from 15 to 80 mol% CeO 2 . In these investigations, Model 3 was applied and a good agreement between SR-XRD and EXAFS results was obtained.…”
Section: Model 3 (N 1 N 2 Free; R 1 = R 2 )mentioning
confidence: 96%
“…Data reduction was performed using the WinXas code (Ressler, 1998) following the procedure described elsewhere (Fá bregas et al, 2006(Fá bregas et al, , 2008. Both pre-and post-edge backgrounds were subtracted from the raw data.…”
Section: Extended X-ray Absorption Fine Structure Analysismentioning
confidence: 99%
“…As far as the authors understand, however, the microstructural analysis of the (U,Zr)O 2 system using Raman spectroscopy has been very rarely carried out. There are previous reports applying Raman spectroscopy to a (Ce,Zr)O 2 , which has the same fluorite structure as (U,Zr)O 2 . Interestingly, it was suggested that ZrO 8 ‐type complex formed at certain Zr doping levels, presumably by incorporation of Zr into the fluorite CeO 2 matrix .…”
Section: Introductionmentioning
confidence: 99%